PENGANGKATAN DAN PEMBERHENTIAN HAKIM MAHKAMAH KONSTITUSI DALAM PRESPEKTIF HUKUM TATA NEGARA (STUDI KASUS PEMBERHENTIAN HAKIM ASWANTO SEBAGAI HAKIM MAHKAMAH KONSTITUSI) - YUNI SALMAH (JURNAL ILMU HUKUM TOPOSANTARO, 2024)
The author’s conclusion: The appointment and dismissal of Constitutional Court judges is based on the provisions of the 1945 Constitution Article 24C paragraph (6) and article 25. The appointment of Constitutional Court judges is then regulated in Articles 15, 16, 18, 19 and 20 and the dismissal of Constitutional Court judges is regulated in Article 23 of Law No.7 of 2020 concerning the Constitutional Court. The appointment and dismissal of Constitutional Court judges based on the Law is intended to maintain the independence of the judiciary and maintain the independence of judicial independence. The dismissal of constitutional judges whose term of office has not expired must refer to Law Number 7 of 2020 concerning the Constitutional Court, specifically Article 23, therefore the dismissal of constitutional judges who do not refer to the Mk Law is declared unconstitutional because it contradicts the 1945 Constitution of the Republic of Indonesia Article 24C paragraph (6) and article 25. Kesimpulan penulis: Pengangkatan dan pemberhentian hakim Mahkamah Konstitusi berdasarkan pada ketentuan UUD NRI 1945 Pasal 24C ayat (6) dan pasal 25. Pengangkatan hakim MK kemudian di atur pada Pasal 15,16,18,19 dan 20 dan Pemberhentian hakim MK diatur Pasal 23 Undang-Undang No.7 Tahun 2020 tentang MK. Pengangkatan dan pemberhentian hakim Mahkamah Konstitusi yang berdasarkan Undang-Undang dimaksudkan agar indenpendensi lembaga peradilan tetap terjaga serta menjaga kemandirian kemerdekaan kekuasaan kehakiman. Pemberhentian hakim konstitusi yang belum habis masa jabatannya harus merujuk pada Undang-Undang Nomor 7 Tahun 2020 tentang Mahkamah Konstitusi, terkhusus pada Pasal 23, oleh sebab itu pemberhentian hakim konstitusi yang tidak mengacu pada UU Mk dinyatakan inkonstitusional karena bertentangan dengan UUD NRI 1945 Pasal 24C ayat (6) dan pasal 25.